Ett skritt fram og ett tilbake TIMSS Advanced 2015 : Matematikk og fysikk i videregående skole. - Grønmo, Liv Sissel (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2016)
This book presents research results from the international comparative study TIMSS Advanced 2015, which investigates the competence of students taking the most advanced courses in mathematics and/or physics in the last year of upper secondary school. This is the third TIMSS Advanced study in which Norway has participated. As a result, we have good data for analyzing trends in competence from the nineties until 2015 for the students in question, which we may call experts in these subjects.